Teacher Innovation in Enhancing Learning Quality through the Tahfidz Al-Qur’an Program: A Phenomenological Study at SMA Muhammadiyah Pontren Imam Syuhodo - Sintya Windi Nur Cahyani; Nurul Latifatul Inayati (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
Quality education requires innovative teachers in managing the learning process. In the context of Islamic education, the Al-Qur'an memorization program is an important innovation that focuses not only on memorization but also on character building and improving the quality of learning. This study aims to describe teacher innovations in optimizing the quality of learning through the tahfidz program at SMA Muhammadiyah Pontren Imam Syuhodo, and to identify obstacles encountered in its implementation. This study uses a qualitative method with a phenomenological approach. Data were obtained through interviews, observations, and documentation involving tahfidz teachers and school officials. Data analysis was conducted using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results show that teachers innovated in four aspects of learning, namely method innovation through the combination of sima'an, independent memorization, and talaqqi; media innovation by utilizing Al-Qur'an manuscripts and audio murottal; strategy innovation through setting flexible memorization targets, providing awards, and tahfidz camp activities; and evaluation innovation through weekly evaluations using mutaba'ah books. The main obstacle faced is the limited time allocated for memorization within the school curriculum. Despite this, teachers continue to strive to develop adaptive strategies to maintain the quality of memorization learning.